A view from the stars - Liu, Cixin (TOR Publishing Group, 2024)
A View from the Stars is a collection of short fiction and nonfiction pieces from Cixin Liu, the New York Times bestselling author of The Three-Body Problem. Included are essays and interviews that shed light on Liu's experiences as a reader, writer, and lover of science fiction throughout his life, as well as short fiction that gives glimpses into the evolution of his imaginative voice over the years"--Back cover.